Genetic variability for and tolerance to anaerobic germination in rice (Oryza sativa L.) (2021)
Poor germination and seedling establishment under flooded conditions is a major bottleneck in the direct-seeding system of rice. The objectives of this study were to determine the genetic variability for traits associated with anaerobic germination and identify tolerant genotypes. One hundred rice genotypes were screened. Data were collected on survival percentage, shoot length, root length, length of plant above water, and seedling vigor index. Six clusters, which were generally related to the ability of the genotypes to tolerate anaerobic germination, were detected. The first two principal components accounted for 91.1% of the total variation, with survival percentage, seedling vigor index and shoot length being the main discriminatory traits. Genotypic coefficient of variation ranged from 18.21% for shoot length to 50.89% for seedling vigor index. Shoot length and seedling vigor index recorded high broad-sense heritability estimates (>60%), with accompanying high genetic advance as percent of mean (>20%); the latter ranged from 23.12% for root length to 82.21% for seedling vigor index. The high heritability, along with high genetic advance, particularly for shoot length and seedling vigor index, indicated that selection for these traits should be effective in improving tolerance to anaerobic germination. Five tolerant genotypes (OBOLO, ART68-12-1-1-B-B, ART64-31-1-1-B-B, CRI-1-21-5-12, and CRI-Enapa) with high survival percentage (≥70%) under anaerobic conditions were identified. These genotypes could be used to improve commercial rice varieties for tolerance to anaerobic germination.